The impact of the expansion of Udon Thani Rajabhat University (Sam Phrao Campus) - Thongwan, Charturon (Journal for Strategy and Enterprise Competitiveness, 2022)
The research is aimed 1) studying the impact of the expansion of Udon Thani Rajabhat University (Sam Phrao Campus) to government organizations, private sector and communities around the university. And 2) Study the preparation method of government organizations, private sector and communities around the university towards the development of urbanization. This is qualitative research; data collection was conducted by in-depth interviews and group interviews including, 10 representatives from government organizations, 2 representatives from the private sector, 10 representatives from the people in the community surrounding the university, total 22 people.The research found the impact of the expansion of Udon Thani Rajabhat University (Sam Phrao Campus) there are many positive effects for government organizations, the private sector and the community surrounding the university such as economic growth, land prices have increased, encouraging the promotion of community education. However, there were many negative consequences as well. The expansion of the university tends to cause urbanization in the community which government organizations, the private sector and communities have guidelines for preparing for changes as well. For example, there should be a police station in the community, infrastructure should be developed in various fields and others.